Effect of Capacity Utilisation on Manufacturing Firms Production in Nigeria (Global Journal of Management and Business Research, 2018)
Despite the significance of capacity utilisation in the production process, it received little attention from development economists especially in Nigeria where capitals were both scarce and under utilised. This present study examined the effect of capacity utilisation on manufacturing firms’ output in Nigeria using time series data covering the period of 1981 to 2016 through an Autoregressive Distributed Lag (ARDL) model approach. The study found positive but insignificant relationship between capacity utilisation and manufacturing firms’ output since capacity was grossly under utilised in virtually every productive firm in Nigeria. Thus, the study concluded that there was substantial under utilisation of capacity in Nigerian manufacturing firms and this under utilisation made positive effect of capacity utilisation less significant in explaining manufacturing firms’ output growth in Nigeria. The study therefore recommended that government and policymakers should make policies that would increase capacity utilisation in manufacturing firms by ensuring appreciation in foreign exchange rate, discouraging uncoordinated imports of goods and services, facilitating access to modern machineries with affordable cost implication, and making stable power supply a priority in Nigeria.
Keywords: capacity utilisation; manufacturing firms; production; actual and potential output; autoregressive distributed lag (ARDL)